Antibacterial activity of actinomycetes associated with clove plant (Syzygium aromaticum) against Staphylococcus aureus and Escherichia coli - Aji, Oktira Roka; Azizah, Mar'atul (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2023)
Actinomycetes form associations with plants through colonizing plant tissues (endophytes) or by residing in the soil around some plants' roots (rhizosphere). Actinomycetes are known to produce antibacterial compounds. This study aimed to investigate the antibacterial activity of actinomycetes associated with the clove plant (Syzygium aromaticum) against Staphylococcus aureus and Escherichia coli. Actinomycetes were isolated from clove plants and the rhizosphere, and their antimicrobial activity against Staphylococcus aureus and Escherichia coli was evaluated using the agar plug method, where the presence of transparent zones around 10-day-old actinomycete growth indicated inhibition of bacterial growth. Four isolates showed inhibitory effects against Staphylococcus aureus, while only three isolates, B.4, T.3, and T.4, demonstrated inhibitory activity against Escherichia coli, as indicated by the presence of inhibition zones. Isolate T.3 exhibited the highest inhibition zone of 8.5 mm against S. aureus, whereas B.4 displayed the highest inhibition zone of 7.7 mm against E. coli. In conclusion, the actinomycetes found in clove plants (Syzygium aromaticum) demonstrate antibacterial properties against Staphylococcus aureus and Escherichia coli, indicating their potential as antibacterial agents.